Gender mainstreaming in root tuber and banana crops seed systems interventions: identification of lessons learnt and gaps - Mudege, Netsayi N.; Torres, S. (International Potato Center, 2017)
Over the years the CGIAR Research Program on Roots, Tubers and Bananas (RTB) has conducted research and developed seed systems’ interventions to promote the availability, accessibility and utilization of clean seed. As part of this work RTB has developed a seed systems framework for intervening in root tuber and banana systems, as well as conducted work to understand gender-related opportunities and constraints for men and women’s participation in RTB seed systems. This report, which is based on the analysis of the publications produced by RTB between 2013 and 2016, seeks to identify the lessons and gaps in mainstreaming gender into seed systems of vegetatively propagated root tuber and banana crops. Evidence from the literature shows that seed systems are socially embedded; so, to develop equitable RTB seed systems researchers and practitioners need to understand the social context in which they aim to intervene. For example, understanding the division of labor in seed production and conservation could help shape the nature of interventions by assisting the managers to identify the methods, measures and strategies to ensure that men and women are able to benefit equally. However, to get this information researchers or project managers need to collect and analyze socioeconomic data, including on gender factors. Additionally, understanding male and female farmers’ knowledge will promote the development of seed systems that are sustainable and responsive to farmers’ needs and capacities.